Chapter 21 Blame Games Stories of Crises, Causes, and Culprits - Resodihardjo, Sandra L. (Taylor & Francis, 2023)
Following a crisis, questions are raised about the event itself, its causes, and its consequences. People wonder how this could have happened and whether it could have been prevented. Depending on how the debate evolves, a blame game will ensue: actors will be held accountable for what happened, and these actors will respond to that blame in various ways. This chapter describes how blame games evolve, who will be blamed, how much blame these actors can expect to receive, and how framing plays a role throughout the blame game. Moreover, particular attention is paid to multilevel blame games as there has been a recent increase in interest in this topic, either through investigating this phenomenon or by pointing out its relevance. This chapter defines and describes what multilevel blame games are while listing future avenues of research.